Teacher Performance in Early Childhood Education: Challenges in Times of Pandemic (Docentes 2.0 Journal, 2023)
Since the emergence of education, teaching performance has been fundamental for constructing teaching situations that lead students to build learning. As an objective, the research had to know the state of the art of the research developed about the teaching performance in initial education during the pandemic. Methodologically, it was based on a study with a narrative design of and of a Documentary-informative type and approached from an eclectic perspective, in which the Scopus, WoS, Scielo, Redalyc, and Google Academic databases were used as a means to retrieve the documents that were selected through a criteria-based sampling, which helped to identify a total of 1433 articles to be reviewed, and that correspond to the period 2020-2021. The results of the review are presented according to two analysis optics: a) the various aspects of teaching performance and b) the implicit components associated with teaching performance. The review allows us to conclude that teaching performance should be observed as a catalytic factor of the changes that aspire to occur in society.
Keywords: Teaching performance; initial education; challenges; pandemic; COVID-19